The relationship between media literacy and teachers’ performance in Tehran - Amiri Dogahe, Hossein; Razmara Meydanghah, Hamideh; Asgarian, Mostafa (Opción, 2019)
This study aimed to investigate the relationship between media literacy and performance among teachers. This research is an applied and correlated one and the statistical population of the research includes all the second stage secondary teachers of district 5 of Tehran who were1952 individuals. Descriptive and inferential statistics including the Pearson correlation coefficient and the Regression tests were used in this study. Results of the research showed that there is a significant relationship between the level of media literacy and teachers’ performance. In conclusion, there is a significant relationship between dimensions of the level of media literacy and teachers’ performance.